Riscos operacionais: uma proposta de modelo de gestão preventiva fundamentada a partir de aspectos da teoria econômica - Fonseca, Leandro Gomes da (2015)
The economic and financial market has directed attention to operational risks and their consequences, given the business processes fragility like financial losses caused by failures and errors coming from people, systems and processes with badly design about corporative goals. The recent financial crisis, largely started by the realization of operational risks which, in turn, began to have a higher incidence of exposure because of globalization and technological advancement. In the rush to protect themselves from the consequences derived from operational risks, companies in various sectors have adopted as a measure of capital retention for protection. However, this mechanism isolated proved insufficient in managing operational risks, indicating the need for further measures and actions to ensure greater security in business management and, consequently, to contribute for economic stability. In this context, this work aims to present a model of preventive and qualitative management of operational risks, as well as highlight the balanced use of capital retention mechanism in an uncertainty scenario. The management model aims to increase the efficiency of business processes to avoid losses arising from failures and people mistakes, systems and poor processes designed, which can be applied to any market segment. As bibliographic references, recent articles on operational risks are analyzed, as well as the theoretical background on some aspects related to the uncertainties of the macro and micro-economic point of view in relation to the management of corporate operational risks. Theories of principal-agent, adverse selection and moral hazard are also analyzed against the operational risk management model proposal, more precisely the conditions to improve analysis, choices and decisions in asymmetric information scenarios. The preventive and qualitative model proposal application will contribute to safer and more efficient structures and businesses processes and thus also contribute to the solvency of corporations